Association between zinc status and autism spectrum disorder in children and adolescents: a systematic review and meta-analysis of case–control studies - Liu, Hezuo; Chen, Ji; He, Jia; Li, Xuening (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to further corroborate a previously reported connection between zinc nutritional status and the occurrence of autism spectrum disorder (ASD) among children and adolescents.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, a systematic review and meta-analysis was conducted. The PubMed, Embase, Web of Science, Scopus, and PsyclNFO databases were searched for all relevant case–control studies published until January 2024. Cohen’s kappa was computed to assess reviewer agreement. This meta-analysis used a random-effects model to summarize the overall association between zinc levels and ASD. The Q-test and I2 statistics were used to evaluate the heterogeneity of the studies, while funnel plots, Begg’s test, and Egger’s test were used to evaluate publication bias.ResultsWe included 25 case–control studies with 4,763 children and adolescents, comprising 2,499 cases and 2,264 typical controls. The random-effects meta-analysis revealed that whole blood and plasma/serum zinc levels were negatively associated with ASD (standardized mean difference [SMD] = −0.44, 95% confidence interval [CI]: −0.63 to −0.25; SMD = −1.79, 95% CI: −2.74 to −0.84), whereas hair (SMD = −0.01, 95% CI: −0.40 to 0.37) and urinary (SMD = −0.17, 95% CI: −0.87 to 0.53) zinc levels were not associated with ASD. Moreover, we observed statistically significant heterogeneity among the included studies (plasma/serum zinc: I2 = 98.8%, P<0.001; hair zinc: I2 = 88.4%, P<0.001; urinary zinc: I2 = 88.0%, P<0.001).ConclusionBlood zinc levels were associated with ASD among children and adolescents. Therefore, screening blood zinc levels in children with ASD may be warranted. Further prospective studies are warranted to elucidate the role of zinc in the etiology of ASD.